Description of three new species of Galethalea Butler, 1876 (Lepidoptera: Erebidae), with comments on the genus - Pinheiro, Lívia R. (Zootaxa, 2016)
Galethalea portoricensis sp. nov. (Holotype male deposited in SMNS: Puerto Rico, 20.iii.1974, W. Plathsr. leg.), G. wolfei sp. nov. (Holotype male deposited in LACM: Colombia, 1.iv.1995, K. Wolfe et al. leg.), and G. machadoi sp. nov. (Holotype male deposited in SMNS: Ecuador, 23.x.2000, G. Brehm leg.) are described, all known only from males. G. machadoi sp. nov. and G. wolfei sp. nov. seem to be closely related to G. davidi Dognin, 1889 resur. stat., while G. portoricensis sp. nov. seems closer to the type species, G. pica (Walker, 1854). The three new species, plus G. davidi, are illustrated in habitus and genitalia, and comments on the genus Galethalea are provided, along with a key to the species currently placed in this genus.